Brazilian Society of Surgical Oncology (BSSO) considerations on oncological thoracic surgery during the COVID-19 pandemic - Carvalho, Erlon de Avila; Rocha, Antônio Bomfim Marçal Avertano; Gross, Jefferson Luiz; Sardenberg, Rodrigo Afonso Silva; da Silva, Ruy Fernando Kuenzer Caetano; Bonomi, Daniel Oliveira; Oliveira, Alexandre Ferreira; Ribeiro, Reitan; Ribeiro, Heber Salvador de Castro; Fernandes, Paulo Henrique de Sousa (Brazilian Journal of Oncology, 2020)
This proposal aims to serve as a tool and assist surgeons in the treatment of thoracic neoplasms during COVID-19 pandemic. It is based on the literature review published so far, in the opinion of individuals specialized in the field of thoracic oncology and not necessarily on evidence-based instructions. We recognize that management strategies are dynamic and must be determined individually, depending on the equipment and tools available for cancer treatment in each institution. In addition, its application will vary according to the severity of COVID-19 in each region.
Keywords: SARS virus; Severe acute respiratory syndrome; Thoracic; Surgery; Surgical oncology